Microbiological Hydroxylation of Cinerone to Cinerolone - Tabenkin, B. (1969)
Cinerone [2-(2′-cis-butenyl)-3-methyl-2-cyclopenten-1-one] is hydroxylated to cinerolone [2-(2′-cis-butenyl)-3-methyl-4-hydroxy-2-cyclopenten-1-one] by a number of streptomycetes, bacteria, and fungi. Aspergillus niger ATCC 9,142 and Streptomyces aureofaciens ATCC 10,762 were found to be the most effective hydroxylators. The optical activity of the product was found to range from [α](D)(25) 0° to -8.6°, depending on the organism and conditions of culture. Two additional hydroxylated products of cinerone have been isolated and identified as 2-n-butyl-4-hydroxy-3-methyl-2-cyclopenten-1-one and 2-(2′-cis-butenyl-4′-hydroxy)-3-methyl-2-cyclopenten-1-one, respectively.